Template‐Free Synthesis of a Molecular Solomon Link by Two‐Component Self‐Assembly. (28th December 2015) - Song, Young Ho; Singh, Nem; Jung, Jaehoon; Kim, Hyunuk; Kim, Eun‐Hee; Cheong, Hae‐Kap; Kim, Yousoo; Chi, Ki‐Whan
Abstract: A molecular Solomon link was synthesized in high yield through the template‐free, coordination‐driven self‐assembly of a carbazole‐functionalized donor and a tetracene‐based dinuclear ruthenium(II) acceptor. The doubly interlocked topology was realized by a strategically chosen ligand which was capable of participating in multiple CH⋅⋅⋅ π and π–π interactions, as evidenced from single‐crystal X‐ray analysis and computational studies. This method is the first example of a two‐component self‐assembly of a molecular Solomon link using a directional bonding approach. The donor alone was not responsible for the construction of the Solomon link, and was confirmed by its noncatenane self‐assemblies obtained with other similar ruthenium(II) acceptors.